ANALISIS PENGARUH BUDAYA ORGANISASI TERHADAP KINERJA PEGAWAI PT. POS INDONESIA CABANG PONTIANAK - Lestari B11108046, Yessi Indah (Jurnal Manajemen Update, 2014)
This study entitled "Analysis of Organizational Culture Influence on Employee Performance PT. Pos Indonesia Cabang Pontianak". This study aims to determine the description of the organizational culture and the employee performance, and the cultural influences on the performance of employees of PT. Pos Indonesia. Forms are used in the research is descriptive research. Techniques of data collection in this study is using questionnaires, interview and literature study. The data analysis technique used is multiple linear regression to analyze the effect of the independent variables which is organizational culture and the dependent variable that is employee performance. Based on the results of the study, concluded that the overall organizational culture and employee performance PT. Pos Indonesia Cabang Pontianak be in good category. From the analysis of multiple linear regression, partial nor simultaneously organizational culture had no effect on performance. Determination analysis (R test) show that organization culture influence on performance had not to much influence that is 25,9%. Keywords: organizational culture and employee performance